PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PEMANFAATAN LIMBAH KULIT KOPI ROBUSTA MENJADI BRIKET (STUDI KASUS PADA IBU RUMAH TANGGA DI DESA HARJOMULYO KECAMATAN SILO KABUPATEN JEMBER) - Nurul Maidah; Titin Kartini (Economic Education, University of Jember, 2015)
The aim of this research is to empower the low economic society of Harjomulyo Village especially the housewife who be a coffee’s farmer and have a limitedness to get a job because of the low education. The researcher collaborate with the one of student from Agriculture Technique Faculty in optimalize the waste of robusta coffee’s bark as the one of nature resourches. The researcher empower by training the housewife to utilize the waste of robusta coffee’s bark to be a briquet. The implementation of empowerment by training not only improve the knowledge and skill that can be a productive activity when the harvest finish, but also the briquet can be an alternative energy subtitute gas and kerosene. Based on the result of the research, briquet not more eficien in using than gas and kerosene. But, because of the simple procedure and the cheap cost, it give the opportunity to the society to increase the income by selling a briquet. This research use the Action Research approach. The data collection methods that use in this research are document method, observation, interview, and Focus Group Discussion (FGD). The Data analysis using the Rapid Rural Appraisal (RRA) method. The purpose of this method is to produce the monitoring about poverty condition at Harjomulyo Village and then make it become reference in producing the planning decision of the tackling poverty and the implementation program.